Macrophage-derived implantable vaccine prevents postsurgical tumor recurrence. (November 2021) - Wang, Dongqing; Xue, Mingming; Chen, Jun; Chen, Heying; Liu, Jiahe; Li, Qianyin; Xie, Yajun; Hu, Yi; Ni, Yilu; Zhou, Qin
Abstract: Immunotherapy emerges as a potential therapeutic strategy against tumor relapse. However, immunosuppressive tumor microenvironment poses an obstacle to immunotherapy. Of particular note is that macrophages are abundant in solid tumors and tumor-associated macrophages (TAMs) are mainly anti-inflammatory and protumoral. Therefore, re-educating TAMs will be critical for improving the antitumor efficacy of immunotherapy. Herein we engineered a macrophage-derived implantable vaccine for suppressing postsurgical tumor relapse. The vaccine comprised hybrid cytomembranes from macrophages/tumor cells and an immunoadjuvant, cytosinephosphate-guanosine oligodeoxynucleotides (CpG ODNs). The vaccine was further embedded into a calcium alginate hydrogel for tissue-localized delivery. Results show that the vaccine could induce the shift from anti-inflammatory M2-like TAMs to proinflammatory M1-like macrophage. Moreover, the vaccine stimulated systemic immunity by facilitating dendritic cells (DCs) maturation and memory T (T EM) cell activation, forming a self-replenishing circulation in tumor microenvironment. Consequently, the vaccine could prevent the postsurgical tumor relapse at both the primary and distant tumor sites. In addition, the lung metastasis was also reduced by the vaccine implantation in mice. The multifunctional vaccine prepared from biomacromolecule and nature-derived material provides a biocompatible and versatile tool for re-educating TAMs and preventing postsurgical tumor recurrence. Highlights: The vaccine induces robust repolarization from anti-inflammatory M2-like TAMs to pro-inflammatory M1-like macrophage. Fused cytomembrane integrates antigenic profile with co-stimulatory molecules to activate synergistic immune responses. Inducing TAMs' reprogramming, antigen replenishment, DCs' antigen presentation to reverse immunosuppression. Combining tissue engineering hydrogel with immunomodulatory cytomembrane to fabricate a biocompatible and versatile vaccine.